Comparative evaluation of the effectiveness of denture cleansers on surface hardness of permanent silicone denture liners - An In vitro study - M Abdul Sameeh; M K Jyothsna; R Nidhin; Prasanth Manohar; S Sreedevi; T P Sasikumar (Wolters Kluwer Medknow Publications, 2021)
Aim: This study aimed to determine the effect of three commercially available denture cleansers on surface hardness of two different silicone denture liners at various time intervals. Materials and Methods: A total of 120 cylindrical specimens of permanent silicone-based soft liners were prepared from a custom made metal mold with dimensions of 15 mm × 10 mm, of which 60 specimens were fabricated using Voco™ and the remaining 60 specimens with Molossil™ permanent denture liners. All specimens were divided into four major groups based on cleansing treatments, comprising 30 specimens each. And then, all cleansers dissolved in 250 mL water as recommended by the manufacturer. Specimens of the first group were cleansed daily by rinsing with water and second group with Periogard™ denture cleansing solution and third group with Secure™ denture cleansing solution and the fourth group with Polident™ denture cleansing solution. Specimens of all groups were tested on 1st week, 1st month, and 6th month time interval using a Shore A Durometer. Three readings were noted for each sample and the mean of those readings was taken. Results: Surface hardness of all the samples was significantly higher after a period of 6 months irrespective of the cleansing treatment. Statistically significant changes were observed between Polident™, Secure™, and Periogard™ denture cleanser groups over control with time. Minor changes were observed in surface hardness of Voco™ denture liners as compared to Molossil™ soft liners for all groups, as time progressed. Conclusion: Voco™ soft denture lining material can be performed significantly better than Mollosil™ soft denture lining material in all cleansing treatments and Polident™ denture cleanser has the least effect on surface hardness of soft liners than Periogard™ and Secure™ denture cleansing agents.